Failure to react positively to flood early warning systems: Lessons learned by flood victims from flash flood disasters: The Malaysia experience - Khalid, Mohamad Sukeri; Mustaffa, Che Su; Marzuki, Mohd Najib; Sakdan, Mohd Fo'ad; Sipon, Sapora; Ariffin, Mohd Taib; Shafiai, Shazwani (World Academy of Science, Engineering and Technology, 2015)
This paper describes the issues relating to the role of the flash flood early warning system provided by the Malaysian Government to the communities in Malaysia, specifically during the flash flood disaster in the Cameron Highlands, Malaysia.Normally, flash flood disasters can occur as a result of heavy rainfall in an area, and that water may possibly cause flooding via streams or narrow channels.The focus of this study is the flash flood disaster which occurred on 23 October 2013 in the Cameron Highlands, and as a result the Sungai Bertam overflowed after the release of water from the Sultan Abu Bakar Dam.This release of water from the dam caused flash flooding which led to damage to properties and also the death of residents and livestock in the area.Therefore, the effort of this study is to identify the perceptions of the flash flood victims on the role of the flash flood early warning system.For the purposes of this study, data were gathered through face-to-face interviews from those flood victims who were willing to participate in this study. This approach helped the researcher to glean in-depth information about their feelings and perceptions of the role of the flash flood early warning system offered by the government. The data were analysed descriptively and the findings show that the respondents of 22 flood victims believe strongly that the flash flood early warning system was confusing and dysfunctional, and communities had failed to response positively to it.Therefore, most of the communities were not well prepared for the releasing of water from the dam which caused property damage, and 3 people were killed in the Cameron Highland flash flood disaster.